LABOR AND GENDER EXPLOITATION IN CHIMAMANDA NGOZI ADICHIE’S AMERICANAH NOVEL: MARXIST FEMINIST ANALYSIS - Anggy Rahayu Larasati; E. Ngestirosa Endang Woro Kasih (Linguistics and Literature Students' Journal, 2023)
This research aims to analyze the Marxist feminist of the novel "Americanah" by Chimamanda Ngozi Adichie, which examines labour exploitation and gender in the novel. The novel explores the experiences of the character Ifemelu through a critical lens, highlighting the gender inequalities that shape her life. This research was conducted using a qualitative descriptive method. The main data source comes from the novel “Americanah”. The data of this research is in the form of narration and dialogue in the novel. This research applies Marxist feminist theory by Karl Marx. This analysis demonstrates how "Americanah" is an effective feminist literature that illuminates the nuanced connection between labour, gender exploitation, and capitalism. Keywords: Americanah, feminist Marxism, gender exploitation, labour, migration